Survival Strategies Of Small and Medium Enterprises Located Aroind Modern Minimarket In Sidikalang Disctrict - Raymon Lampadosma Siregar (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study aims to identify the survival strategies of small and medium enterprises (SMEs), specifically traditional grocery stores, located near modern minimarkets in Sidikalang District, Dairi Regency. A qualitative descriptive method was used with 40 grocery store owners as respondents. The findings reveal that all stores (100%) sell staple goods such as rice, sugar, and cooking oil, while 55% offer 3 kg LPG gas, which is not available in minimarkets. Differentiation strategies include providing local products and meeting specific customer requests, such as fresh vegetables and single-item sales. All stores remain competitive by offering lower prices and discounts to loyal customers. About 67.5% of stores operate with monthly capital of IDR 4,000,000–6,000,000, and 77.5% experienced a decline in customers following the arrival of minimarkets. Most stores (80%) are strategically located, although 95% lack adequate parking facilities. Additionally, 75% offer home delivery services, and all apply personal approaches such as allowing purchases on credit and having flexible operating hours. Emotional connections with customers serve as the primary strength in sustaining these businesses.